Sex difference in heart failure risk associated with febuxostat and allopurinol in gout patients - Cheng, Ching-Lan; Yen, Chi-Tai; Su, Chien-Chou; Lee, Cheng-Han; Huang, Chien-Huei; Yang, Yea-Huei Kao (Frontiers in Cardiovascular Medicine, 2022)
Background Gout or rapid reduction in serum uric acid level may increase the incidence of heart failure (HF). To compare the risk of HF between febuxostat and allopurinol in gout patients with coexisting cardiovascular (CV) diseases, the varying severity would be likely to confound the risk estimation. Gout and HF are both sex-related diseases, and the risk difference from the urate-lowering agents between women and men remains unknown. Aims To evaluate the HF hospitalisations risk of febuxostat and allopurinol in gout patients in real-world settings. Methods A population-based cohort enrolled patients with allopurinol or febuxostat initiation from 2011 to 2018. Participants were grouped into, without (low CV risk group) or with (high CV risk group) a history of recent major CV admission. The primary outcome was HF hospitalization. The secondary outcomes were composite CV events, all-cause mortality, and the cause of CV mortality. We used the ‘as-treated' analysis and Cox proportional hazards model after propensity score (PS) matching. Patients were further stratified into men and women to evaluate the gender differences. Results Febuxostat users had a significantly higher risk of HF hospitalization than allopurinol users in gout patients either with low CV risk [hazard ratio (HR) 1.39; 95% confidence interval (CI) 1.25–1.55] or high CV risk [HR 1.36; 95% CI 1.22–1.52]. Particularly, women with gout had a higher risk of HF hospitalization than men. Conclusion The HF hospitalization risk was highest in gout women with high CV risk and febuxostat use. Monitoring of HF is warranted in these patients.